Synthesis and Characterization of Triamine modified coated Iron Sand Hybrid Nanomaterials originating from Kendal Coast - Ricka Prasdiantika; Susanto Susanto; Yustika Kusumawardani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Nanomaterials have broad and unique applications in various fields. In this research, synthesis of Iron Sand Magnetic Hybrid nanomaterials coated with propyldiethylenetriammine modified silica (PB@SiO2@TA) originating from the coast of Muara Kencan, Kendal Regency. This study began with iron sand preparation, continued with activation, dispersing iron sand, then coating iron sand with propyldiethylenetriammine modified silica. The resulting product was characterized by X-Ray Fluorescence (XRF), Fourier Transform Infrared (FT-IR) Spectrophotometer, X-Ray Diffractometer (XRD), and Transmission Electron Microscope (TEM). The characterization results show that the iron sand of the coast of Muara Kencan Beach has a high iron oxide content (81.66%) with minerals in the form of magnetite. The characterization results also showed that the nanomaterial hybrid iron sand coated with propyldiethylenetriammine modified silica (PB@SiO2@TA) was successfully synthesized with a crystal size of 36.21 nm, with better particle dispersion than the prepared iron sand.